Acceptance of alternative forms of family life by students of the Bialskie region - Ruszkowska, Marzena (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2015)
The article describes the popularity of alternative forms of family life among young people living in urban and rural settings of the Bialski region. It contains a discussion of the results of a survey conducted at the turn of 2013/2014, and an attempt to answer the question whether and, if so how, informal relationships are an alternative to marriage and family, whether young people are aware of the legal consequences of staying in socalled free relationships, and whether they have an impact on a child if it results from such a relationship.
Keywords: alternative forms of family life; Bialski region; threats to family life